Monopole Antenna Design Analysis for TNI AD Satellite Telecommunication - Rohadi, Erfan; Arga Yoda, Vincensius; Datumaya Wahyudi Sumari, Arwin (International Journal of Frontier Technology and Engineering, 2022)
Antenna that is made dynamically, light and cheap are the characteristics of microstrip antenna. Microstrip antennas have the characteristics of working at high frequencies according to the antenna calculations if the dimensions are small, the working frequency becomes high frequency. So the monopole microstrip antenna is the solution to the existing military communications. This research will study a monopole antenna design with small dimensions using parameters in millimeters (mm). This antenna works at a working frequency of 3.73 GHz. The substrate used has a size of 99.53 mm x 84.35 mm with a thickness of 0.787 mm, = 4.4×10−12F·m−1 and an impedance of 50 . Antenna performance can be seen from the value of Return Loss, Bandwidth, VSWR, and Radiation Pattern of the antenna. The simulation result data is presented using the WIPL-D software based on the Method of Moment. This indicates that at 3.73 GHz the highest gain value is 5.4 dB, VSWR 1.46 with a bandwidth of 10.18% and a return loss of -14.44 dB. This result is sufficient to meet the satellite communication in the coverage area of ​​the C Band which works in the frequency range of 3-4 Ghz.